2014
DOI: 10.1089/jwh.2013.4523
|View full text |Cite
|
Sign up to set email alerts
|

On-Site Comprehensive Curriculum to Teach Reproductive Health to Female Adolescents in Kenya

Abstract: Important misconceptions and gaps in reproductive practices were identified and addressed using a mixed methods approach. Despite prior basic knowledge and positive attitudes on STI prevention and family planning, complementary teaching approaches were instrumental in improving overall knowledge of STIs other than HIV as well as family planning. The curriculum was feasible, well received, and achieved its educational goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
0
7
0
3
Order By: Relevance
“…However, such programs to enhance reproductive health knowledge would require a different approach to ensure participation of both men and women. Educational programs targeting women’s health education were found to be effective in improving their knowledge and reproductive health behaviour [38, 39]. Studies have found that SRH educational programs had greater impact on maternal health behaviors when both spouses are involved compared to when only women participated the program [40].…”
Section: Discussion and Policy Recommendationsmentioning
confidence: 99%
“…However, such programs to enhance reproductive health knowledge would require a different approach to ensure participation of both men and women. Educational programs targeting women’s health education were found to be effective in improving their knowledge and reproductive health behaviour [38, 39]. Studies have found that SRH educational programs had greater impact on maternal health behaviors when both spouses are involved compared to when only women participated the program [40].…”
Section: Discussion and Policy Recommendationsmentioning
confidence: 99%
“…Thus far, efforts towards improving HIV-related knowledge in Sub-Saharan Africa have encompassed a wide variety of intervention types and methods of disseminating HIV-related information, such as peer education [ 7 – 9 ], game-based education [ 10 ], skill-building interventions [ 11 , 12 ], and mass media campaigns [ 13 ]. Many such interventions have drawn on various theoretical frameworks, such as social cognitive theory [ 8 , 14 ], the theory of planned behaviour [ 12 ], and the theory of reasoned action [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the 455 identified records, 20 studies met the inclusion criteria [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of interventions (n = 13) targeted adolescents 10-19 years old, and two also included youths of 20-24 years old. Adolescents benefited from sexuality education were of both sexes; however, three studies targeted only girls [29,35,39]. One program provided sexuality education to students with learning disabilities [27] and one to orphan adolescent girls [35].…”
Section: General Description Of Included Interventionsmentioning
confidence: 99%